Update on trichoscopy: Integration of the terminology by systematic approach and a proposal of a diagnostic flowchart. Issue 1 (22nd November 2021) - Kinoshita‐Ise, Misaki; Sachdeva, Muskaan
Abstract: Trichoscopy represents a non‐invasive diagnostic modality widely used in daily practice. Despite the common perception that this technique has been fairly established, some key issues remain to be addressed. Complexity and inconsistency in terminology in past literature are likely to confuse investigators when they are recording, reporting, and retrieving the findings. In addition, a diagnostic algorithm adopting sufficiently integrated and updated findings is not readily available. By adopting a systematic review approach, this review attempted to redefine major trichoscopic findings and integrate their synonyms individually into the most frequently used terms besides identifying and discussing terms which potentially cause confusion. The findings are categorized into five subgroups: hair shaft, follicular, perifollicular, scalp findings, and hair distribution pattern abnormalities. The calculation of sensitivities and positive predictive values of such redefined findings was conducted by reviewing the descriptions in the past literature on major hair diseases, including alopecia areata, androgenetic alopecia/female pattern hair loss, telogen effluvium, trichotillomania, lichen planopilaris, frontal fibrosing alopecia, central centrifugal cicatricial alopecia, discoid lupus erythematosus, folliculitis decalvans, tinea capitis, and dissecting cellulitis, to confirm the diagnostically meaningful findings for representative diseases. This attempt redefined, for instance, yellow dots, short vellus hairs, exclamation mark hairs, black dots, and broken hairs as the findings of diagnostic significance for alopecia areata and hair diameter diversity, peripilar sign, and focal atrichia for androgenetic alopecia/female pattern hair loss. An updated diagnostic flowchart is proposed with the instructions to maximize its usefulness. Current limitations and future perspectives of trichoscopy as well as other emerging non‐invasive diagnostic modalities for hair diseases are also discussed.